Dari Manual ke Digital: Evolusi Akuntansi UMKM di Era Teknologi - Budi Asmarawati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to provide a comprehensive understanding of the implementation of digital accounting among SMEs in the Sleman region. Using a descriptive qualitative method, the research involved direct interviews with three SME owners: Mrs. Riska (a processed cracker seller), Mr. Agus (a retail grocery owner), and Mrs. Sri (also a processed cracker seller). The results of the study show that out of the three, only Mr. Agus has adopted digital financial record-keeping. Meanwhile, Mrs. Riska and Mrs. Sri still use manual methods with handwritten records. This is due to a lack of understanding and awareness of the importance of maintaining accurate and organized financial reports. Therefore, the study suggests involving the government and relevant institutions to provide comprehensive support and education to SMEs on the benefits and methods of implementing digital accounting. Through an interactive approach, it is expected that SME owners will find it easier to understand and use digital accounting technologies, thereby minimizing the risk of recording errors and maximizing the benefits of technology in their business operations.